The Euro/Dollar exchange rate: Chaotic or non-chaotic? - Daniela Federici; Giancarlo Gandolfo (Center for Economic Studies and ifo Institute (CESifo), 2011)
The aim of this paper is to develop a continuous time exchange rate model that allows for heterogeneity of the agents' beliefs, in order to explore non-linearities and possible chaotic behaviour. The theoretical model contains an intrinsic non-linearity that gives rise to a jerk differential equation, which is in principle capable of generating chaos. The model is econometrically estimated in continuous time with Euro/Dollar data and examined for the possible presence of chaotic motion. Our results indicate that the possibility of chaotic dynamics has to be rejected.
Keywords: F31; F37; C49; C61; 330; exchange rate; chaos; jerk equation; continuous time econometrics; Euro; US-Dollar; Wechselkurs; Wechselkurstheorie; Chaostheorie; Schätzung; EU-Staaten; USA